Analysis of Service Effectiveness For Health Insurance Participants at Kuta Utara Community Health Center, Badung Regency - I Gede Sukma Okta Perdana; I Made Agus Mahendra; Ni Luh Putu Widyantari (International Journal Labs, 2025)
This study aims to analyze the implementation of health services, measure the quality of public services, in this case the quality of services for health insurance participants and know and analyze the extent of the satisfaction level of health insurance participants at the North Kuta Health Center according to the perspective of the customers served. The North Kuta Health Center is a health service in the North Kuta sub-district area by providing health services using health insurance. The implementation of the assessment is measured through various indicators such as service procedures, service requirements, clarity of service officers, discipline of service officers, ability of service officers, speed of service, politeness and friendliness of officers, certainty of service costs, certainty of service schedules, environmental comfort and safety. The research method used is a mixed method between qualitative and quantitative with data collection techniques through questionnaires accompanied by in-depth interviews from respondents/resource persons. The results of the study on 300 respondents to fill out a questionnaire were in accordance with the opinion of each respondent about the services they received from what they got complete with their reasons. As well as interdepth interviews from resource persons conducted for 3 months starting from May to July 2024. The assessment was very good, but it was necessary to re-evaluate to get better research results, because this study was carried out in a short time and the coverage of the area was relatively small.